2018
DOI: 10.1177/1054773818756987
|View full text |Cite
|
Sign up to set email alerts
|

Animal-Assisted Intervention and Dementia: A Systematic Review

Abstract: This review discusses the relationship between animal-assisted interventions (AAI) and behavioral and psychological symptoms of dementia (BPSD). A systematic search was conducted within CINAHL, Web of Science CAB Abstracts, PubMed, Abstracts in Social Gerontology, Google Scholar, and PsycINFO for primary research articles. A total of 32 studies were included in the final review. Variation was noted in study designs and in study setting. Twenty-seven of 32 studies used dogs as the intervention. Agitation/aggres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
82
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(90 citation statements)
references
References 35 publications
(132 reference statements)
7
82
0
Order By: Relevance
“…A recent systematic review by Yakimicki et al . discussed the relationship between AAIs and the occurrence of behavioural and psychological symptoms of dementia . The majority of the 32 studies included in the review highlight various benefits of using AAI to alleviate some symptoms or to improve social behaviour.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review by Yakimicki et al . discussed the relationship between AAIs and the occurrence of behavioural and psychological symptoms of dementia . The majority of the 32 studies included in the review highlight various benefits of using AAI to alleviate some symptoms or to improve social behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…8,[14][15][16][17][18][19] A recent systematic review by Yakimicki et al discussed the relationship between AAIs and the occurrence of behavioural and psychological symptoms of dementia. 20 The majority of the 32 studies included in the review highlight various benefits of using AAI to alleviate some symptoms or to improve social behaviour. However, there were some important limiting factors, such as widely varying study designs and statistical methods, making it difficult to compare studies.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on AAI with supportive findings have involved older adults with dementia (Dell, et al, 2018;Yakimicki, Edwards, Richards, & Beck, 2018), elderly adults (Bernabei et al, 2013;Berry et al, 2012;Bert et al, 2016;Holt, Johnson, Yaglom, & Brenner, 2015;Virués-Ortega et al, 2012), and adults with intellectual disabilities (Maber-Aleksandrowicz, Avent, & Hassiotis, 2016) and cognitive impairment (Hu, Zhang, Leng, Li, & Chen, 2018). The benefits of AAI have also been reported through research with adults in corrections (Burger, Stetina, Turner, Mcelheney, & Handlos, 2011;Dell & Poole, 2015), adults recovering from surgery (Havey et al, 2014), adults and children in varying hospital wards (Bert et al, 2016;Phung et al, 2017;Silva & Osório, 2018;Stefanini et al, 2016;Stempien, et al, 2019), people who use drugs (Burger et al, 2011;, and university or college students (Barker et al, 2016;Bell, 2013;Binfet, 2017;Binfet & Passmore, 2016;Binfet & Struik, 2018;Crossman et al, 2015;Dell et al, 2015;Grajfoner et al, 2017;Jarolmen & Patel, 2018;Stewart et al, 2014).…”
Section: Animal-assisted Interventionsmentioning
confidence: 96%
“…Scientific studies have shown proof of concept for animal assisted interventions and reported promising findings for a range of psychosocial, emotional, and physiological outcomes across the life span 78910. One randomised pilot study, for example, tested a cognitive behavioural intervention teaching dog training skills (“how to be a good dog trainer”) to children with attention deficit/hyperactivity disorder.…”
Section: From Dogs To Dolphinsmentioning
confidence: 99%